Notes on a small collection of thecate hydroids (Cnidaria: Hydrozoa)from Tristan da Cunha, south Atlantic - Galea, Horia R. (Zootaxa, 2010)
A pilot survey of the shallow-water, thecate hydroid fauna of Tristan da Cunha archipelago, was undertaken for the first time. The examination of the collected material revealed the presence of at least sixteen hydroids, of which three could not be identified to species level in the absence of fertile specimens. Two sympatric morphotypes, provisionally assigned to Halecium delicatulum Coughtrey, 1876, are described, along with a discussion on the astonishingly wide morphological variation attributed to this taxon. All the present species are illustrated, and some of them are either described or accompanied by brief remarks. Only twelve hydroids were previously reported from the study area and the present report adds eleven new records to the list of known species, bringing their number to twenty-three.